Non-linear effects at ionization of hydrogen atoms in the strong pulsed light field - Starodub, S.S.; Roshchupkin, S.P. (Вопросы атомной науки и техники, 2012)
It is a model theoretical work of the applied character in which: outside the framework of the dipole approximation
(with an accuracy of about v/c) the effective interaction force between two atoms of hydrogen at their ionization in a
pulsed field of two opposite laser wave is theoretically studied. It is shown that the effective interaction force between
hydrogen ions (atoms after ionization), can become an attractive force on certain time intervals in the presence of
the pulsed laser field. As a result the pulsed laser field can slow down backward motion of ions in 6 times. Вне рамок дипольного приближения (с учетом поправок v/c) теоретически изучена эффективная сила взаимодействия между двумя атомами водорода при их ионизации в присутствии внешнего импульсного поля двух лазерных волн, распространяющихся навстречу друг другу. Исследуется возможность максимального сближения атомов водорода и удержание атомов за счет импульсного внешнего поля. Поза рамками дипольного наближення (з урахуванням поправок v/c) теоретично вивчена ефективна сила взаємодії між двома атомами водню за їх іонізації в присутності зовнішнього імпульсного поля двох лазерних хвиль, що розповсюджуються назустріч одна одній. Досліджується можливість максимального зближення атомів водню і утримання їх за рахунок зовнішнього імпульсного поля.